Exosome-derived CIRP: An amplifier of inflammatory diseases - Han, Jingrun; Zhang, Yibo; Ge, Peng; Dakal, Tikam Chand; Wen, Haiyun; Tang, Shuangfeng; Luo, Yalan; Yang, Qi; Hua, Bianca; Zhang, Guixin; Chen, Hailong; Xu, Caiming (Frontiers in Immunology, 2023)
Cold-inducible RNA-binding protein (CIRP) is an intracellular stress-response protein and a type of damage-associated molecular pattern (DAMP) that responds to various stress stimulus by altering its expression and mRNA stability. Upon exposure to ultraviolet (UV) light or low temperature, CIRP get translocated from the nucleus to the cytoplasm through methylation modification and stored in stress granules (SG). During exosome biogenesis, which involves formation of endosomes from the cell membrane through endocytosis, CIRP also gets packaged within the endosomes along with DNA, and RNA and other proteins. Subsequently, intraluminal vesicles (ILVs) are formed following the inward budding of the endosomal membrane, turning the endosomes into multi-vesicle bodies (MVBs). Finally, the MVBs fuse with the cell membrane to form exosomes. As a result, CIRP can also be secreted out of cells through the lysosomal pathway as Extracellular CIRP (eCIRP). Extracellular CIRP (eCIRP) is implicated in various conditions, including sepsis, ischemia-reperfusion damage, lung injury, and neuroinflammation, through the release of exosomes. In addition, CIRP interacts with TLR4, TREM-1, and IL-6R, and therefore are involved in triggering immune and inflammatory responses. Accordingly, eCIRP has been studied as potential novel targets for disease therapy. C23 and M3, polypeptides that oppose eCIRP binding to its receptors, are beneficial in numerous inflammatory illnesses. Some natural molecules such as Luteolin and Emodin can also antagonize CIRP, which play roles similar to C23 in inflammatory responses and inhibit macrophage-mediated inflammation. This review aims to provide a better understanding on CIRP translocation and secretion from the nucleus to the extracellular space and the mechanisms and inhibitory roles of eCIRP in diverse inflammatory illnesses.